Diagnosis of Oestrus ovis infestation in sheep by PCR and enzyme-linked immunosorbent assay - Bello, Hornblenda Joaquina Silva [UNESP]; Lins, José Gabriel Gonçalves [UNESP]; Silva, Naiara Mirelly Marinho da [UNESP]; Albuquerque, Ana Cláudia Alexandre de [UNESP]; Amarante, Mônica Regina Vendrame [UNESP]; Kozlowski Neto, Vitoldo Antonio [UNESP]; Amarante, Alessandro F.T. [UNESP] (Elsevier, 2022)
The aim of this study was to assess the suitability of PCR and ELISA as diagnostic method in young sheep naturally infested by Oestrus ovis larvae. The experiment was carried out from December 2020 to April 2021 with 39 lambs divided into two groups: infested (n = 26) and control treated group (n = 13). The infested group did not receive treatment against oestrosis, and the control group was treated with closantel (10 mg/kg orally) every 28 days in order to keep the animals as free as possible of O. ovis infestation. The clinical signs varied among animals regardless of the number of recovered larvae of each lamb, however, the thick mucus and mucopurulent nasal discharge scores were less frequent in lambs from treated group. There was no correlation between the nasal discharge score and the number of O. ovis recovered larvae (R² = 0.012, P = 0.165). Three control treated animals only presented first instar larvae (L1) (1 – 4 larvae/animal) which were smaller than L1 found in the lambs of the infested group. Ninety-two percent of the lambs from infested group (24/26) were parasitized by O. ovis with number ranging from 1 to 54 larvae per animal. A gradual increase in plasma IgG (anti-antigen of O. ovis larvae) levels of animals from infested group after the third week of the trial was observed, whereas the control lambs had low levels of IgG until the end of the experiment. The PCR had low sensitivity (26 %) and high specificity (100 %), and it presented poor agreement (k = 0.177) with the larvae detection after the lamb slaughter. The oestrosis clinical signs were not related to larvae infestation intensity and ELISA showed a greater advantage over the PCR technique in identifying animals that are carrying O. ovis.
Keywords: Bot fly; ELISA; Lamb; Molecular diagnostic; Oestrosis